FAUNA IKAN DIPERAIRAN SEKITAR BUKIT LAWANG KAWASAN TAMAN NASIONAL GUNUNG LEUSER [The Fish Fauna of Bukit Lawang Waters Areas in Gunung Leuser National Park] - Haryono Haryono (Masyarakat Iktiologi Indonesia (Indonesian Ichthyological Society), 2006)
Gunung Leuser National Park lays areas North Sumatera and Nanggroe Aceh Darussalam Provinces. The study on fish fauna in this area was done especially at Bukit Lawang waters. The aims of the study were to describe fish diversity, status and its potency. There is 32 fish species were found that belongs to 26 genera and 15 families. Cyprinidae is dominant family: with 10 species. The potency is 11 consumed fish and 11 ornamental fish, and 9 species for both ornament and consumption.